Between plunder and shock - Adriana Castro (Oñati Socio-Legal Series)
This document highlights that the Peruvian State took advantage of the pandemic as an opportunity to infringe upon the rights of indigenous peoples by accelerating the prior consultation processes in the mining sector, thus violating rights recognized in its own legislation and the jurisprudence of the Inter-American Court. The analysis of consultation processes (2020-2022) evidenced (I) lack of accessibility, as the State used legal Spanish in all process documents, despite the fact that in 77.7% of the communities, over 80% of the population had an indigenous language as their mother tongue; (II) lack of good faith, as 88% of the cases had stages shortened and the intercultural dialogue stage excluded; and (III) the failure to aim at reaching an agreement, using less time and recording only a matrix of agreements from one community.